Zinzendorfs "Residenz" in Westminster 1737: eine Suche nach Eindrücken und Erlebnissen - Dose, Kai (Unitas Fratrum, 2018)
In order to be able to conduct important negotiations with the Georgia Trustees and with Anglican church leaders in person, Zinzendorf stayed in Westminster from the end of January until the beginning of March 1737. Numerous letters and notes report on what happened, but Zinzendorf never described his stay in detail. This means that, while those matters that are important for church history are well known, seemingly unimportant aspects of his stay have been lost from sight. It is with these that this article is concerned. The people who helped the count to find a suitable 'residence' when he arrived in London are introduced. Research shows how events that could not have been planned helped Zinzendorf to achieve success. For example, in Westminster he encountered General Oglethorpe, who had returned from Georgia quite unexpectedly: he generously assisted the count with his knowledge and contacts. The house that Zinzendorf rented placed him in the midst of the institutions with which he wanted to hold conversations. The article indicates where this house was, which rooms it offered and how they may have been used, and also who owned it. In the extensive gardens that belonged to it there stood an architecturally unique 'temple' -- a visible sign of the convictions of the landlord, who was a leading freemason. The author's researches create the impression that Zinzendorf had to seek the way to achieve his goal and that he used the house cleverly to that end. He held preaching services to which people from the upper and lower classes were admitted. By doing this he both witnessed to his faith and at the same time built up new networks of contacts. In founding the Order of the Mustard Seed he created an international community of faith. The author's researches make clear that Zinzendorf had to realize his plans and convictions in impressive circumstances and that it was not infrequently luck that enabled him to do so.